Naval Defense Strategy for Naval Base Resilience Through Spectromar Maritime Surveillance Utilization - Adriyanto, Agus; Prakoso, Lukman Yudho; Susmoro, Harjo; Suseto, Buddy; Warka, I Wayan (CV. Publikasi Indonesia, 2025)
This research aims to formulate an effective maritime defense strategy in increasing the resilience of the Indonesian Navy base through the use of SpectroMar Maritime Surveillance technology. The background of this research is based on the complexity of maritime threats that continue to grow and the limitations of conventional surveillance systems. The method used is a quantitative approach with analysis based on the theoretical framework of Clausewitz's strategy (Ends, Ways, Means). The results of the study show that the integration of SpectroMar is able to improve early detection capabilities, rapid response, and coordination efficiency between bases. The resulting strategy recommends improving infrastructure, training personnel, and strengthening cross-agency cooperation. This research is expected to be a reference in strengthening the national sea defense system that is adaptive, intelligent, and sustainable.